Comunhão e missão presbiteral ontem e hoje. Discernimentos e compromissos - Suess, Paulo (Revista eclesiástica brasileira, 2010)
In order to be able to establish a dialogue with the modern world, the Vatican II listened critically to the modernity. A Vatican III would have to be prophetically counter-cultural, “untune the choir of the satisfied” and challenge many hegemonic values of consumerism, accumulation and acceleration. In this scenario of multiple pathologies of the late modernity, the presbyters’ mission demands discretion and commitment. The elementary priest experiences the prophetic counter-culture in the pilgrim’s modesty (vs. consumerism), in the Eucharistic gratuity (vs. accumulation) and as an emergency brake in a “train” called barbarism (vs. acceleration). The presbyter, who is part of the culture he questions, finds his roots in the word and in the experience of the God-Love with its extensions in the celebration of the sacraments, as effective word, and in the services of justice, charity and mercy, as contextually incarnated word.